In Search of Self: A Qualitative Study of the Life-Career Development of Rural Young Women. - Shepard, Blythe (Canadian Journal of Counselling and Psychotherapy, 2007)
Little attention has been paid to the life-career development of rural adolescents. The aim of this project is to explore the hopes, beliefs, and fears of eight young women and aspects of their rural environment that act to constrain or enhance their options. Participants constructed life-space maps, possible selves, and photographic displays during two semi-structured interviews. Four themes emerged across the transcripts: (a) just like living under a microscope; (b) empowering and disempowering relationships; (c) opening and limiting conditions; and (d) aspirations and apprehensions. Implications for practice and future research are discussed.